Company Responsibilities to Maternity Leave Workers Who are Not Given Wages in Terms of Employment Law - Nurdiansyah, Lucky Alfian; Sari, Wiwit Juliana; Kurniati, Yeti (Formosa Journal of Sustainable Research, 2024)
The fulfilment of women workers' rights must be given more attention, in order to maintain their health and not interfere with their work productivity. The research aims to analyse the company's responsibility in fulfilling the full wage rights of female workers during maternity leave based on Law Number 13 of 2003 concerning Manpower and Government Regulation Number 78 of 2015 concerning Wages and identify legal remedies that can be taken by female workers to demand the fulfilment of full wage rights during maternity leave. This research uses an empirical juridical approach method with descriptive analytical research specifications.  Data analysis is carried out using qualitative methods. Companies have the responsibility to provide compensation in the form of wage payments to female workers who take maternity leave. This obligation is based on Article 84 of Law Number 13 of 2003 concerning Labour and Article 31 of Government Regulation Number 78 of 2015 concerning Wages. Female workers who experience obstacles in fulfilling their maternity leave rights can take legal remedies based on Law Number 2 of 2004 concerning Industrial Relations Dispute Resolution.  These legal remedies include bipartite negotiations, tripartite negotiations, and a lawsuit to the Industrial Relations Court